The problem of legal pluralism (Società e diritti, 2017)
The author–beginning from the criticism of the essay of Alexander Catelani, “Il diritto come forma e come struttura”–turns his analysis toward the theme of the juridical pluralism. Legalreality  is  in  constant  change,  such  that it is impossibleto  be exclusivelydescribed by  the conceptof “hierarchy”(of  the  norms  and  of  the  juridical orders)  that,  instead,  in  the perspective of legal positivism, was looked out as exclusive.Key words:legal positivism, juridical pluralism,Latin America